2022
DOI: 10.1186/s13195-021-00940-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MCP-1 and changes on cognitive function in community-dwelling older adults

Abstract: Background Monocyte Chemoattractant Protein-1 (MCP-1), a glial-derived chemokine, mediates neuroinflammation and may regulate memory outcomes among older adults. We aimed to explore the associations of plasma MCP-1 levels (alone and in combination with β-amyloid deposition—Aβ42/40) with overall and domain-specific cognitive evolution among older adults. Methods Secondary analyses including 1097 subjects (mean age = 75.3 years ± 4.4; 63.8% women) fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
0
8
1
Order By: Relevance
“…This finding has been corroborated by Takahachi et al, who reported that live P. gingivalis downregulated MCP-1 expression in cell culture [ 63 ]. Furthermore, MCP-1 levels have been shown to inconsistently affect Aβ status and deposition [ 64 ]. Although insignificant, elevated Aβ42/40 coupled with downregulation of MCP-1 had a higher magnitude of association with cognitive decline compared to elevated Aβ42/40 coupled with upregulation of MCP-1 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has been corroborated by Takahachi et al, who reported that live P. gingivalis downregulated MCP-1 expression in cell culture [ 63 ]. Furthermore, MCP-1 levels have been shown to inconsistently affect Aβ status and deposition [ 64 ]. Although insignificant, elevated Aβ42/40 coupled with downregulation of MCP-1 had a higher magnitude of association with cognitive decline compared to elevated Aβ42/40 coupled with upregulation of MCP-1 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, MCP-1 levels have been shown to inconsistently affect Aβ status and deposition [ 64 ]. Although insignificant, elevated Aβ42/40 coupled with downregulation of MCP-1 had a higher magnitude of association with cognitive decline compared to elevated Aβ42/40 coupled with upregulation of MCP-1 [ 64 ]. Moreover, MCP-1 also plays a role in tau phosphorylation and the formation of neurofibrillary tangles [ 63 , 65 ] indicating a possible role of MCP-1 in cognitive decline and AD evolution.…”
Section: Resultsmentioning
confidence: 99%
“…MCP-1 (Monocyte chemoattractant protein-1), a beta chemokine, has been associated with various neuroinflammatory disorders, such as multiple sclerosis (MS), Alzheimer's disease (AD), and Parkinson's disease. Notably, high Serum levels of MCP-1 levels are increased in mild cognitive impairment and mild AD 47 49 . Similarly, IL-8 cytokine is associated with neuroinflammatory disorders, and CBD significantly mitigated the LPS-induced NF-κB activity, IL-8, and MCP-1 in human macrophages 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory or chemoattractant cascades are also altered in AD. For instance, the monocyte chemoattractant protein-1 (MCP-1), during chronic inflammation, contributes to an overactivity and excessive recruitment of inflammatory cells, which leads to neuronal damage and cognitive decline [ 59 ]. Inflammation and aging are determining factors that affect innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%